NUMERICAL ANALYTIC SOLUTION TO UNMIXED AXISYMMETRIC PROBLEMS OF THERMOELASTICITY FOR CONTINUOUS-INHOMOGENEOUS IN DEPTH HALF-SPACE - Sergey M. Aizikovich; Leonid I. Krenev (Advanced Engineering Research)
The numerical analytic solution to the unmixed axisymmetric problems of thermoelasticity for the continuous-inhomogeneous in depth half-space at the given heat sources and force action on its surface is offered. Hankel integral transform apparatus is used for the solution of the boundary value problem. The impact of variable in depth thermomechanical parameters in the boundary layer on the temperature field distribution, heat flow and face slip is analyzed.